STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA SI UNTUANG SUDAH DI KANAGARIAN SALIDO SARI BULAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Sari, Fitri Marta; Hayati, Yenni; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This article was structure and social function of folklore legend Si Untuang Sudah in Kanagarian Salido Sari Bulan District IV Jurai Pesisir Selatan Regency. Indonesian Literature Study Program, Department of Language and Literature of Indonesia, Faculty of Languages and Arts, State University of Padang. This study aims to describe the structure, and the functions contained in the story of Si Untuang Sudah in Kanagarian Salido Sari Bulan District IV Jurai Pesisir Selatan Regency. This research type is qualitative research by using descriptive method. Data were collected through interview, observation and recording with informant in Kanagariani Salido Sari Bulan District IV Jurai Pesisir Selatan Regency. Based on the research findings concluded the following matters. Structure of the story of Si Untuang Sudah can be described as folows: (a) figures of the legend Si Untuang Sudah, while the additional characters are Puti Linduang Moon, Rajo Angek Garang, Rajo Kuaso Kakek tuo, community (b) The path contained in legend Si Untuang is conventional groove; (c) there are several backgrounds contained in the story of Si Untuang Sudah, time setting, place, and social background. (d) The theme of the legend of Si Untuang has been about the greatness of God in showing his power; (e) The mandate we can take in the story is not to be emotional, do not be easy to believe in others, always be grateful and say thank you for what God has given you, to be wise before making a decision. The social function of the legend story of Si Untuang Sudah is for educating. entertaining, forming identity and tradition.Keywords: Structural, Social function, Folklore, Legend